Quantifying the structure of the woody element in Savannahs using integrated optical and Synthetic Aperture Radar (SAR) approach : a stepping stone towards country wide monitoring in South Africa - Mathieu, Renaud (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.